Peran Mahasiswa Program Asistensi Mengajar di SMAN Lombok Timur - Zahara, Laxmi; Nuraini; Hidayatullah, Zul; Ariandani, Nunung (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
Teaching assistance activities are activities that encourage students to master various knowledge and skills that are useful for entering the world of work. The teaching assistance activities carried out by Hamzanwadi University students at SMAN 1 Pringgasela and SMAN 1 Sukamulia were carried out well. Implementing activities begins with debriefing, releasing students at school, observing, implementing, and withdrawing students. Students gain additional knowledge and experience while interacting with the school. Universities, schools, and students alike have had a positive impact. The results obtained from this activity for students are; 1) increase students' knowledge and experience regarding classroom management and making learning tools 2) can develop a responsible and disciplined attitude, 3) improve independent performance, and 4) increase social sensitivity and concern or empathy for society and the environment, 5) train 4 competencies teacher for prospective teacher students.